(untitled) (Bangladesh Journal of Urology, 2025)
Background: Antimuscarinic drugs are used for the treatment of overactive bladder (OAB), as it effectively reduces detrusor overactivity and bothersome storage symptoms in LUTS. However, the use of antimuscarinic agent is associated with several side effects such as dry mouth and constipation. Mirabegron is a selective beta-3 agonist that has good safety and tolerability profile with lower incidence of adverse events. Objective: To evaluate the effectiveness and safety of Mirabegron as add-on therapy for persistent storage symptoms under tamsulosin monotherapy for benign enlargement of prostate. Methods: This prospective observational study was conducted at OPD, Department of Urology, National Institute of Kidney Diseases & Urology (NIKDU), Dhaka, from January 2021 to February 2022. Finally A total of 108 patients with persistent storage symptoms after 12 weeks of tamsulosin monotherapy with benign enlargement of prostate were purposively included in the study. Patients with post-void urine volume (PVR) >50 mL, prostate size < 40gm, history of urinary retention, neurogenic bladder, urethral stricture and taking any anti-muscarinic drugs, uncontrolled diabetic mellitus, bladder and prostate carcinoma were excluded from the study. Mirabegron (25 mg once daily) was added to Tamsulosin. Before and 12 weeks after addition of either drugs, International Prostate Symptom Storage Sub Score (IPSS-S), Overactive Bladder Symptom Score (OABSS), Quality of life(QOL) were assessed, Uroflowmetry and transabdominal ultrasound was done to assess maximum flow rate, voided volume (Qmax) and PVR respectively. Adverse events were recorded throughout the study period. Results: The mean ages of the patients were 61 ±5.5. The mean IPSS-S, QOL, OABSS significantly reduced after three months of treatment (p<0.001). 13 (12%) patients developed adverse effects (dry mouth 1.8%, dysuria 2.8%, acute urinary retention 0.9%, constipation 2.8%). Conclusion: Mirabegron with tamsulosin as add-on therapy for persistent storage symptoms significantly improved storage symptoms. There is no significant treatment emerging adverse events (TEAE) in mirabegron. Bangladesh J. Urol. 2024; 27(2): 137-142